Iridoschisis and keratoconus in a patient with severe allergic eye disease and compulsive eye rubbing: a case report. (December 2016) - Yusuf, Imran; Salmon, John
Abstract Background Iridoschisis is a rare disorder characterized by splitting of the anterior and posterior iris stroma, resulting in disintegrated iris fibrils which float freely in the anterior chamber. We report an exceptional case of bilateral iridoschisis occurring in conjunction with keratoconus and severe allergic eye disease. Case presentation A 24-year-old white man had had periocular contact dermatitis and allergic eye disease from the age of 3 years. He was allergic to grass, animal hair, and pollen and worked grooming horses. He compulsively rubbed his eyes. There was no history of previous blunt trauma to either eye. There were signs of bilateral iridoschisis and keratoconus with allergic conjunctivitis, all of which were more severe in his right eye. An open drainage angle was identified bilaterally on gonioscopy, excluding primary angle closure. There was no evidence of glaucoma in either eye. Conclusions There are two previous cases reporting the combination of iridoschisis and keratoconus, but no clear common etiology has been identified. In this case there was no evidence of angle closure but there were signs of allergic conjunctivitis. This amalgamation of signs might be explained on the basis of habitual eye rubbing. Treating the allergic eye disease has attenuated this behavior.